Are Meniere's disease patients with otolith organ impairment more likely to have balance dysfunction?. (2nd November 2019) - Zhou, Yu-Juan; Li, Qing-Zhong; Gao, Ying-Qi; Gao, Lin-Xi; Zhao, Zhi-Xiang; Wu, Yong-Zhen; Wang, Jing
Abstract: Background: Patients with Meniere's disease (MD) may present with peripheral vestibular end organ dysfunction and balance dysfunction. Objective: This study aimed to compare the results of vestibular evoked myogenic potential (VEMP) tests with those of the sensory organization test (SOT) in patients with MD to determine whether they are correlated. Material and methods: In total, 132 patients with unilateral MD were evaluated using an audiometric test, the SOT, a caloric test and VEMP tests. Results: Cervical VEMP and ocular VEMP tests were conducted in 132 patients with MD, and the response rates of the affected side were lower than those of the unaffected side. The composite score, C5 ES, and C6 ES of the SOT were significantly decreased in patients with no VEMP responses compared to those with VEMP responses. Conclusions and significance: MD patients with no VEMP responses are more likely to develop balance impairment than those with VEMP responses. MD patients with otolith organ impairment may therefore have balance disorders, and should exercise caution to prevent falls and subsequent injuries.